1999
DOI: 10.1038/sj.bjc.6690224
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase 2 is up-regulated and localized to macrophages in the intestine of Min mice

Abstract: Summary Expression of cyclooxygenase 2 (COX-2) is believed to play an important role in adenoma formation in murine polyposis models, and inhibition of COX-2 activity may, at least, partly explain the chemopreventative activity of non-steroidal anti-inflammatory drugs against colorectal cancer in humans. However, the mechanism by which COX-2 acts in intestinal tumorigenesis remains unresolved because of conflicting data on the cellular localization of COX-2 in intestinal mucosa. Using immunohistochemistry with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
63
2
4

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(80 citation statements)
references
References 29 publications
11
63
2
4
Order By: Relevance
“…However, at an earlier stage of carcinogenesis, in benign human colorectal adenomas or polyps (which represent a more relevant target for chemoprevention), COX-2 is expressed predominantly by stromal cells (as well as by dysplastic epithelial cells), the majority of which have been identified as CD68-positive inflammatory mononuclear cells or macrophages (Bamba et al, 1999;Muller-Decker et al, 1999;Chapple et al, 2000;Hull et al, 2000b;Soslow et al, 2000;Hardwick et al, 2001;Khan et al, 2001;Takeuchi et al, 2002). A similar pattern of COX-2 expression has also been noted in tumours from several murine intestinal tumorigenesis models (Oshima et al, 1996;Taketo, 1998;Hull et al, 1999;Shattuck-Brandt et al, 1999, although there appears to be increased heterogeneity in the COX-2-expressing stromal cell population in mice compared with humans (Taketo, 1998;Hull et al, 1999;Shattuck-Brandt et al, 1999. Stromal mononuclear cell (as well as epithelial cell) COX-2 expression has also been observed in other premalignant conditions of the human gastro-intestinal tract, including Barrett's oesophagus (Fu et al, 1999;Morris et al, 2001) and Helicobacter pylori-associated chronic gastritis (Wilson et al, 1998;Sung et al, 2000).…”
Section: Introductionmentioning
confidence: 77%
“…However, at an earlier stage of carcinogenesis, in benign human colorectal adenomas or polyps (which represent a more relevant target for chemoprevention), COX-2 is expressed predominantly by stromal cells (as well as by dysplastic epithelial cells), the majority of which have been identified as CD68-positive inflammatory mononuclear cells or macrophages (Bamba et al, 1999;Muller-Decker et al, 1999;Chapple et al, 2000;Hull et al, 2000b;Soslow et al, 2000;Hardwick et al, 2001;Khan et al, 2001;Takeuchi et al, 2002). A similar pattern of COX-2 expression has also been noted in tumours from several murine intestinal tumorigenesis models (Oshima et al, 1996;Taketo, 1998;Hull et al, 1999;Shattuck-Brandt et al, 1999, although there appears to be increased heterogeneity in the COX-2-expressing stromal cell population in mice compared with humans (Taketo, 1998;Hull et al, 1999;Shattuck-Brandt et al, 1999. Stromal mononuclear cell (as well as epithelial cell) COX-2 expression has also been observed in other premalignant conditions of the human gastro-intestinal tract, including Barrett's oesophagus (Fu et al, 1999;Morris et al, 2001) and Helicobacter pylori-associated chronic gastritis (Wilson et al, 1998;Sung et al, 2000).…”
Section: Introductionmentioning
confidence: 77%
“…In accordance with this finding, COX-2 expression has already been demonstrated in interstitial cells of human colon adenomas and carcinomas. 12,14,36 Some authors found that COX-2-positive interstitial cells correspond mainly to macrophages [10][11][12] but others demonstrate COX-2 expression mainly in fibroblasts. 13,14 Our results indicate that superficial fibroblasts and myofibroblasts may express cytoplasmic PLA2 as well as COX-2 and are thus in accordance with these latter studies.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] In colon adenomas and carcinomas, COX-2 is overexpressed in tumor cells but also in interstitial stromal cells. [10][11][12][13][14] COX-2 overexpression in interstitial stromal cells also induces tumor angiogenesis in several models of tumor development. 15,16 In intestinal tumors, angiogenesis induced by COX-2 expressing interstitial stromal cells is mediated by prostaglandin E2 through EP2 prostaglandin E2 receptor signaling.…”
mentioning
confidence: 99%
“…Increased levels of COX-2 in macrophages have been reported in human CRC and mouse models of CRC. 39,[58][59][60][61] COX-2 expression is regulated at both the transcriptional and posttranscriptional levels, and the signaling pathways involved in COX-2 transcriptional regulation include NF-kB, PI3K/AKT, GSK/b-catenin, and MAPKs. 29 High expression of active MAPKs has been observed in the stroma of human colonic adenomatous polyps.…”
Section: Discussionmentioning
confidence: 99%